Stagnating Jatropha Biofuel Development in Southwest China: An Institutional Approach - Jia Li; Bettina Bluemling; Arthur P. J. Mol; Thomas Herzfeld (Sustainability, 2014)
Biodiesel from jatropha has been considered as a promising alternative to fossil fuels for some time. Consequently, China started promoting jatropha as one of the options to meet its ever-increasing energy consumption, and the Chinese biodiesel industry also gained interest. However, the excitement of the biofuel industry in jatropha faded after it did not bring about the expected results. This article investigates the stagnation in jatropha development and production for biodiesel in China, using two detailed case studies of jatropha biofuel production in southeast China. It is found that the underdeveloped biodiesel policy and regulation, such as a rather late formulation of standards for biodiesel (especially the B5) and the absence of mandatory targets, is an important reason for hampering jatropha development. Besides that, lack of financial support undermined sustained jatropha planting at the farm level and lack of sustained commitment from state-owned enterprises or private companies over a long time span further contributed to jatropha project's failure. Better implementation of the rule of law, mandatory blending requirements, hazard insurance, as well as continuous financial support, might improve the continuation of jatropha plantation schemes.
Keywords: 330; oil companies; smallholders; discourses; biodiesel; Sichuan; Guangxi